Supervision of the Implementation of Road Maintenance in the Department of Public Works and Urban Planning - Anhar Yani; Muhammad Lufi Fadhillah; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze Supervision of The Implementation of Road Maintenance in The Department Of Public Works And Urban Planning. The Public Works and Spatial Planning Office of the City of Banjarmasin has not been effective because there are roads that are not in accordance with the needs of the community, this is because the roads are functioning does not cover the entire project. The inhibiting factors in supervising road and road construction projects concern (1) a lack of quality of road supervisors, (2) the lack of funding for road supervision so far is still very minimal, and (3) the condition Inadequate work infrastructure and facilities at the public works and spacial planning office.